Big Data Analytics 10th International Conference, BDA 2022, Hyderabad, India, December 19-22, 2022, Proceedings - Roy, Partha Pratim; Agarwal, Arvind; Li, Tianrui; Krishna Reddy, P.; Uday Kiran, R. (Cham : Springer Nature Switzerland : Imprint: Springer, 2022)
This book constitutes the proceedings of the 10th International Conference on Big Data Analytics, BDA 2022, which took place in Hyderabad, India, in December 2022. The 7 full papers and 7 short papers presented in this volume were carefully reviewed and selected from 36 submissions. The book also contains 4 keynote talks in full-paper length. The papers are organized in the following topical sections: Big Data Analytics: Vision and Perspectives; Data Science: Architectures; Data Science: Applications; Graph Analytics; Pattern Mining; Predictive Analytics in Agriculture.
Big Data Analytics: Vision and Perspectives -- Data Challenges and Societal Impacts - the case in favor of the Blueprint for an AI Bill of Rights -- Big Data in Cognitive Neuroscience: Opportunities and Challenges -- Data Science: Architectures -- A Novel Feature Selection Based Text Classification using Multi-layer ELM -- ARCORE: Software Requirements Dataset for Service Identification -- ARCORE: Software Requirements Dataset for Service Identification -- Learning enhancement using Question-Answer generation for e-book using contrastive fine-tuned T5 -- Data Science: Applications -- A Machine and Deep Learning Framework to Retain Customers based on their Lifetime Value -- A Deep Learning based Approach to Automate Clinical Coding of Electronic Health Records -- Determining the severity of Dementia using ensemble learning -- Determining the severity of Dementia using ensemble learning -- A distributed ensemble machine learning technique for emotion classification from vocal cues -- Graph Analytics. -Drugomics: Knowledge Graph & AI to Construct Physicians' Brain Digital Twin to Prevent Drug Side-effects and Patient Harm -- Extremely Randomized Tree based Sentiment Polarity Classification on Online Product Reviews -- Community Detection in Large Directed Graphs -- Pattern Mining -- FastTIRP: Efficient discovery of Time-Interval Related Patterns -- Discovering Top-K Periodic Patterns in Temporal Databases -- Hui2Vec: Learning Transaction Embedding Through High Utility Itemsets -- Predictive Analytics in Agriculture -- A Data-driven, Farmer-oriented Agricultural Crop Recommendation Engine (ACRE) -- Analyze the Impact of Weather Parameters for Crop Yield Prediction using Deep Learning -- Analysis of Weather Condition based Reuse among Agromet Advisory: A Validation Study.
Keywords: Data mining; Machine learning; Computers, Special purpose; Social sciences-Data processing; Education-Data processing; Data Mining and Knowledge Discovery; Machine Learning; Special Purpose and Application-Based Systems; Computer Application in Social and Behavioral Sciences; Computers and Education